Isolated Hyperglycemia at 1 Hour on Oral Glucose Tolerance Test in Pregnancy Resembles Gestational Diabetes Mellitus in Predicting Postpartum Metabolic Dysfunction - Retnakaran, Ravi (American Diabetes Association, 2008)
OBJECTIVE—Gestational impaired glucose tolerance (GIGT), defined by a single abnormal value on antepartum 3-h oral glucose tolerance test (OGTT), is a metabolically heterogeneous disorder. Indeed, the antepartum metabolic phenotype of women with a single abnormal value at 1 h during the OGTT (1-h GIGT) resembles that of women with gestational diabetes mellitus (GDM), whereas GIGT at 2 or 3 h (2/3-h GIGT) is similar to normal glucose tolerance (NGT). Thus, we hypothesized that 1-h GIGT would be associated with the same adverse outcomes as GDM, i.e., increased infant birth weight and postpartum metabolic dysfunction. RESEARCH DESIGN AND METHODS—A total of 361 women underwent an antepartum glucose challenge test (GCT) and a 3-h OGTT, assessment of obstetrical outcome at delivery, and metabolic characterization by OGTT at 3 months postpartum. The antepartum GCT/OGTT identified five study groups: GDM (n = 97), 1-h GIGT (n = 28), 2/3-h GIGT (n = 34), abnormal GCT NGT (abnormal GCT with NGT on OGTT) (n = 128), and normal GCT NGT (normal GCT with NGT on OGTT) (n = 74). RESULTS—Caesarian section rate was higher in women with 1-h GIGT, but birth weight did not differ significantly between the non-GDM groups (P = 0.1978). At 3 months postpartum, glycemia (area under the glucose curve) progressively increased across the groups from normal GCT NGT to abnormal GCT NGT to 2/3-h GIGT to 1-h GIGT to GDM (P < 0.0001), while both insulin sensitivity (IS(OGTT)) and β-cell function (insulinogenic index/homeostasis model assessment of insulin resistance [HOMA-IR]) progressively decreased (P = 0.002 and P < 0.0001, respectively). The strongest independent negative predictors of insulinogenic index/HOMA-IR were GDM (t = −4.1, P < 0.0001) and 1-h GIGT (t = −3.8, P = 0.0002). CONCLUSIONS—Like GDM, 1-h GIGT is associated with postpartum glycemia, insulin resistance, and β-cell dysfunction.